The Effectiveness of Self-Management Education on Reducing Blood Glucose Levels in Patients with Type II Diabetes Mellitus in the Working Area of UPT Puskesmas Paleleh, Buol Regency - Budi Utomo; Rona Febriyona; Nur Uyuun I. Biahimo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Diabetes mellitus can increase mortality rates globally, nationally, and locally, and may cause severe long-term complications if not properly managed. One of the ways to control this problem is through the implementation of diabetes self-management education. The purpose of this study was to determine the effectiveness of self-management education in reducing blood glucose levels among patients with Type II Diabetes Mellitus in the working area of UPT Puskesmas Paleleh, Buol Regency. This study employed a pre-experimental method with a One Group Pretest-Posttest design. The population consisted of 42 respondents, selected using a purposive sampling technique. Data analysis was conducted using the SPSS program with the Wilcoxon Signed-Rank Test, a non-parametric comparative statistical test. The results showed that the effectiveness of diabetes self-management education on reducing blood glucose levels in patients with diabetes mellitus obtained a p-value = 0.000 with alpha < 0.05. Based on the results of the study, it can be concluded that self-management education is effective in reducing blood glucose levels among patients with Type II Diabetes Mellitus in the working area of Puskesmas Paleleh, Buol Regency. This study is expected to serve as a reference for improving health services and to contribute ideas and references for future research.